Perbandingan Hasil Belajar Geografi Menggunakan Model Take And Give Dan TPS Berbantuan Media Kartu SMAN 8 Banda Aceh - Fitriani Yulianti; Nurul Hafilda (Program Studi Pendidikan IPS Unesa, 2022)
Education can experience changes for the better so that there is a need for renewal. The teaching model is said to be relevant if it is able to lead students to achieve their educational goals. The Take And Give and Think Pair Share models are learning models that use group work and collaboration systems. The purpose of this study was to compare the learning outcomes of geography using the Take and Give and Think Pair Share models assisted by card media in class X students of SMA Negeri 8 Kota Banda Aceh. This research uses a quantitative approach with the type of Quasi Experiment research. The population in this study were all students of class X SMA Negeri 8 Banda Aceh City. Sampling using the Purposive Sampling Technique, two research classes were taken, namely X IPS 1 with 30 students and X IPS 2 with 30 students. Data analysis techniques in the form of initial ability analysis, normality test, homogeneity test, and hypothesis testing. Data were processed using the t-test with normal and homogeneous requirements. Based on hypothesis testing shows that tcount > ttable so that Ha is accepted. The results showed that the learning outcomes of geography taught by the Take and Give model were better than those taught by the Think Pair Share model assisted by card media in geography subject class X IPS SMA Negeri 8 Kota Banda Aceh.